Kepemimpinan Transformasional, Humanistik dan Menghargai bagi Lulusan Sekolah Inspektur Polisi (SIP), terhadap Generasi Milenial dan Generasi Z - Himawan, Agung - (Pusat Penelitian dan Pengembangan Polri, 2024)
The aim of this research is to explore strategies for leading personnel from the millennial generation and generation Z so that they become leaders who are transformative, humanistic and love their members. This research method uses a type of article review writing, where primary data and secondary data are obtained from books, journal articles and on-line articles. The research results show that (1) indicators of transformational leadership style in Police Inspector School graduates as agents of change can be seen from the ability to provide motivation, inspiration, foster member innovation, provide intellectual stimulation, clarify the roles of personnel, build solid team work and has charisma, especially towards the millennial generation and generation Z; (2) The impact of transformational leadership that is humanistic and respectful will be able to reduce negative behavior that tends to be indifferent, want to be appreciated and lazy and realize their creative and innovative self-actualization, especially completing tasks through new methods and using digital technology. The conclusion that can be obtained is that the transformational, humanist and respectful leadership style is very suitable to be applied to the millennial and generation Z groups and it is hoped that this writing will be useful as a reference for graduates of the Police Inspector School (SIP).